The Use of Ultrasound Contrast in Interventional Radiology - Tantrige, Priyan; Ballal, Khalid; Kelly, Michael; Stefanidis, Konstantinos; Huang, Dean; Sidhu, Paul S.; Yusuf, Gibran Timothy (The Arab Journal of Interventional Radiology, 2023)
Ultrasound contrast agents have gained increasing popularity due to the high level of safety, real-time improved visualization, and ability to detect vascularity. As a result, contrast-enhanced ultrasound lends itself well to interventional radiology including in preprocedure assessment, intraprocedural guidance, and postprocedure evaluation. The authors aim to demonstrate the wide utility of contrast-enhanced ultrasound in both vascular and nonvascular intervention.
Keywords: contrast agent; contrast medium; ultrasound